THE CIVILIZATIONAL HEGEMONY IN THE WAR ON TERROR - PETER BAOFU (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
At a time when “individual terrorism” becomes such an ineffable evil in the mind of many (especially of the Americans since the September 11 attacks in 2001), it is unthinkable to even say anything more impartial about it. Yet, contrary to the belief of many contemporaries, “individual terrorism” by the weak against the strong is important to civilization, as an opposing form of violence against “state terrorism” and “state-sponsored terrorism” by the strong against the weak.1 Two questions are in order. Firstly, is individual terrorism necessarily undesirable? And secondly, if so, is it possible to eradicate individual terrorism? Perhaps the U.S. war on terror since 2001 is a good case study here to answer the two questions, to be addressed hereafter, in that order.